NEWS TEXT DISCOURSE ANALYSIS MODEL SARA MILLS AT MEDIA ONLINE DETIK.COM (GISELLA ANASTASIA PORN VIDEO CASE) - Eka Yudha Prasetya; Catur Suratnoaji (Universitas Islam Balitar, 2022)
The news of the viral pornographic video case involving Gisella Anastasia in the detik.com news portal received high attention from the public. The comments column on news portals is filled with various kinds of public opinion. The researcher chose 2 corpus of news from detik.com news portal on the day of the incident. The data obtained were then analyzed using the Sara Mills discourse analysis method. From the discussion, the researcher sees that Gisella Anastasia as a woman and a public figure is shown as a negative character in this case. In addition, Gisel is also positioned as an object in several sentences in the 2 selected news corpus. The researcher sees that the patriarchal discourse in Indonesia still positions women and public figures as figures who have high news value, and are vulnerable to being positioned unequally. The discourse of patriarchal ideology is still visible in several narratives and readings of the production and consumption of public discourse on news portals in particular and public discourse in general.